Assessment and classification of chronic pruritis and its relation to systemic diseases - Alyamani, Nawal Rajeh; Almutairi, Noura Talal; Alkhamis, Riam Saleh; Brnawa, Rehab Bakr; Badeghaish, Samah Omar; Alhazmi, Renad Ghazi; Hilmi, Rana Mohammed; Alfakeeh, Abeer Hassan; Abushanab, Orjuwan Maher; Abdullah, Ruya Adel; Alhakeem, Wadiah Mahdi; Safar, Mohammed Ahmed (International Journal Of Community Medicine And Public Health, 2021)
Although pruritis might not be a serious condition with significant healthcare impacts, it is usually associated with an unpleasant sensation that leads to scratching the skin. It has been demonstrated that the severity of the condition is significantly variable and ranges between disabling and mild conditions. Chronic pruritis has been defined as the presence of daily itching for >6 months. In the present literature review, we have discussed the different approaches that have been previously indicated to assess and evaluate chronic pruritis, and the classification of the condition its relation to the different systemic diseases. The classification of chronic pruritis can be done using a clinical or an etiological diagnosis. The clinical diagnosis is usually based a primary skin condition, while the etiological diagnosis is based on the presence of different diseases that may be systematic, neurological, or psychiatric disorders. Accordingly, conducting a thorough examination is essential to establish a proper diagnosis before adequately managing the affected patients. Furthermore, the treatment of the underlying etiology should also be adequately considered for adequate management and enhanced prognosis.